Notice of the Excavation of a Cairn at Mossknowe, on the Kirtle Water, Dumfriesshire - Bate, Dorothea M A (Proceedings of the Society of Antiquaries of Scotland, 1909)
Report of the excavation of a cairn in May 1908, led by Dorothea M A Bate. The creation of a trench and removal of clay revealed an encircling ditch and two stone slabs, without tools marks. At the bottom of the cist, the unburnt human remains of one or two adults with a child or children were uncovered. No pottery or weapons were found. Bate concludes the burial would have been of considerable importance due to the size of the cairn and its central position.